Placing the Past and Moving the Present: Myth and Contemporary History in Telefolmin - Jorgensen, Dan (Culture, 1990)
A striking feature of myth among the Telefolmin of Papua New Guinea is the way in which narrative events are situated in known and named places. Myth’s inscription on the landscape contributes to ritual’s evocative power, but, beyond this, it gives myth a bridgehead in the everyday world that invites a mythic construction of contemporary events. Using the visit of Papua New Guinea’s Governor General as an example, I argue that Telefolmin were able to effectively mobilize the power of the sacred site of Telefolip — and its mythic associations — in novel historical circumstances, a possibility enabled by myth’s presence in particular places. Sacred sites are not only places where things happened: they are also places where things continue to happen.